Investor Psychology, Mood Variations, and Sustainable Cross-Sectional Returns: A Chinese Case Study on Investing in Illiquid Stocks on a Specific Day of the Week - Ying, Qianwei; Yousaf, Tahir; Ain, Qurat ul; Akhtar, Yasmeen (Frontiers in Psychology, 2020)
This paper uncovers a new finding of sustainable cross-sectional variations in stock returns explained by mood fluctuations across the day of the week. Long/short leg of illiquid anomaly returns are extensively related to the day of the week, and magnitude of excess returns is also striking. The speculative leg of illiquid anomalies is the long leg (Birru 2018). Therefore, the long (speculative) leg experiences sustainable high returns on Friday than short (non-speculative) leg. At the same time, relatively higher long (speculative) leg returns witnessed on Friday than Monday with greater magnitude difference. These cross-sectional variations in illiquid stocks on specific days are consistent with the explanation of limit to arbitrage. The observed variations in cross-sectional returns are sustained and consistent with the plenty of evidence from psychology research regarding the low mood on Monday and high mood on Friday